RESPON PERTUMBUHAN DAN HASIL TANAMAN SAWI PAGODA DAMPAK PEMUPUKAN PUPUK ORGANIK CAIR - Astutik, Astuttik; Sumiati, Astri; Sutoyo, Sutoyo; Demus, Niko (Universitas Tribhuwana Tunggadewi, 2024)
The research aims to obtain the right type and dose of Liquid Organic Fertilizer to obtain optimal growth and yields of Pagoda mustard plants. The study used a factorial Completely Randomized Design, namely two kinds of Liquid Organic Fertilizer (cow urine and rabbit urine) and the dosage consisted of 4 levels (0, 600, 1.200,1.800 ml) so that there were 8 treatment combinations (P1D0, P1D1, P1D2, P1D3, P2D0, P2D1, P2D2, P2D3) and repeated 4 times. Observations include parameters: plant height, number of leaves, length, and width of leaves, diameter of the hood, wet weight of the plant, and dry weight. The research results showed that the type and dose of LiquidOrganic Fertilizer interacted with each other to support the growth of pagoda mustard greens, 1,200 ml/l cow urine liquid organic fertilizer produced the best growth. Both POC cow urine and rabbit urine produce insignificant fresh plant weight, and a POC dose of 1,200 - 1,800 ml/l was able to produce the best plant results.